Aridity‐Driven Non‐Linear Shift of Plant Sodium Allocation Strategy at Regional and Global Scales - Hongbo Guo; Jiahui Zhang; Xiaoyan Kang; Cong Yu; Nianpeng He (Global Ecology and Biogeography, 2025)
Aim Plants allocate sodium (Na) to leaves and roots as an adaptation to salinity and drought, potentially modulating herbivory and ecosystem carbon cycling. However, large‐scale spatial patterns and environmental drivers of plant Na allocation remain unclear. Location China and the world. Time Period Field data were collected between 2013 and 2019. Literature data were collected between 1970 and 2024. Major Taxa Studied Vascular plants. Methods We compiled a global database of paired leaf Na (Na Leaf ) and root Na (Na Root ) content, combining field observations from 2183 species across 72 Chinese ecosystems with globally synthesised literature records. Results The spatial pattern of plant Na allocation between leaves and roots is primarily regulated by aridity. Generally, plants allocate more Na to roots in humid zones but more to leaves in arid zones. Furthermore, aridification leads to abrupt and non‐linear increases in the Na Leaf to Na Root ratio (Na Leaf:Root ) when aridity exceeds the critical threshold (0.814 for the Chinese plant species and 0.774 for the Chinese plant community). Importantly, the threshold response is consistently observed from species to community levels and from China to global biomes. Main Conclusions Our findings demonstrate the flexible allocation of plant Na in response to salinity and drought on a large scale. Projected aridification could amplify leaf Na allocation in threshold‐exceeding regions, possibly enhancing the activity of herbivores and decomposers and triggering cascading impacts on plant community structure and carbon cycling rate.